Investigation of the effect of directivity pulses on the seismic response of a curved RC bridge - Kardoutsou, Vassiliki; Angelidakis, Vasileios; Psycharis, Ioannis; Taflampas, Ioannis (International Journal of Applied Engineering Research, 2019)
Within the near-fault zone, ground motions are influenced by the rupture mechanism and directivity phenomena. Near-fault ground motions are of special interest in Earthquake Engineering, as they might result in large inelastic displacements of structures. In this paper, an investigation is presented concerning the effect of the directivity pulses inherent in near-fault ground motions on the inelastic response of a curved RC bridge, specifically Bridge G7 of Egnatia Highway in Greece. The analyses were performed for a sample of 90 near-fault seismic records. From each record, the first six pulses were extracted and simplified ‘pulse records’ were defined, composed of one or more (up to six) pulses. First, a pushover analysis was performed and, based on the derived yield acceleration corresponding to the bilinear representation of the capacity curve, each record was scaled to three intensity levels, corresponding to behavior factors qy = 2, 3 and 4. Non-linear time-history analyses were then performed for each original record and the related ‘pulse records’ using OpenSees. By comparing the results, conclusions were drawn on the significance of each pulse to the nonlinear response. To this end, the errors for several general and local response quantities were calculated. The results show that the maximum inelastic deformations occur for the ground motions for which the elastic fundamental period of the bridge is close to one half of the period of the predominant pulse. Also, in most cases, the maximum response for the original record could be adequately estimated by the response for the ‘pulse record’ consisted of only two (and in few cases of three) pulses, especially when the fundamental period of the bridge was in between the periods of these pulses.<br
Keywords: Near-fault; Directivity pulse; Nonlinear response; Time-history analysis; Synthetic ground motions; Bridges